МАКТАБГАЧА ЁШДАГИ БОЛАЛАРГА РИТОРИКАНИ ЎРГАТИШ ВА РИВОЖЛАНТИРИШ КОМПЕТЕНЦИЯЛАРИ - Шамуратова, Х.Қ. (SCIENCE and SOCIETY, 2025)
The article discusses the formation of linguistic thinking in preschool children in the process of studying rhetoric. Rhetoric forms in children not only knowledge, oral communication skills, but also oratory ideals, tastes, attitudes, and ideas of general cultural significance.